A new species of Palpares Rambur (Neuroptera: Myrmeleontidae) with an identification key to the species of West Africa - (:unkn) unknown (My University, 2011)
Palpares longimaculatus nov. sp. is described from West Africa. This species resembles P. radiatus Rambur, 1842 and P. incommodus (Walker, 1853) from the same region and is very similar to P. kalahariensis Stitz, 1912 from South Africa. The characters differentiating these species are indicated. An identification key to the West African species of Palpares is provided and all the keyed species are illustrated.
Keywords: African Research